Analisis Strategi Inovasi dan Keunikan Produk Terhadap Keunggulan Bersaing - Haura Ananda Putri; Muhammad Danial, R. Deni; Mulia Z, Faizal (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2025)
The development of time and technology has an impact on human life, especially in today's business world. Business growth in the culinary sector such as cafes and restaurants. In the city of Sukabumi, the growth of this type of catering business is quite high. The growing business in the culinary world will lead to increasingly fierce competition, with a variety of increasingly diverse food and beverage menus that can offer new product innovations in unique types and flavors as well as services and good facilities. The aim of this study was to determine the impact of the company's innovation strategy and product uniqueness on increasing competitive advantage. The research method used is a quantitative method with a descriptive and initiative approach. The sampling method used in this study was non-probability sampling with a saturated sampling method where 50 café and restaurant owners in Cikole District, Sukabumi City were selected as respondents. The data analysis technique used in this study is multiple linear regression. The results of the study based on the simultaneous test (F-test) and partial test (T-test) show that innovation strategy and product uniqueness have a significant effect on increasing competitive advantage. The results of the correlation test with SPSS version 25 show that the innovation strategy and product uniqueness have a value of 0.880 in increasing competitive advantage, which means that these results have a “very good” influence and a positive relationship. The results of the test of determination with innovation strategy and product uniqueness in increasing competitive advantage are 77.5%, while the remaining 22.5% is due to the influence of other factors outside this study.